THE PARASITOID, Cotesia flavipes (CAMERON) (HYMENOPTERA: BRACONIDAE), INFLUENCES FOOD CONSUMPTION AND UTILIZATION BY LARVAL Diatraea saccharalis (F.) (LEPIDOPTERA: CRAMBIDAE) - Rossi, Guilherme Duarte [UNESP]; Salvador, Gabriela; Consoli, Fernando Luis (Wiley-Blackwell, 2014)
Parasitoids exploit host insects for food and other resources; they alter host development and physiology to optimize conditions to favor parasitoid development. Parasitoids influence their hosts by injecting eggs, along with a variety of substances, including venoms, polydnaviruses, ovarian fluids, and other maternal factors, into hosts. These factors induce profound changes in hosts, such as behavior, metabolism, endocrine events, and immune defense. Because endoparasitoids develop and consume tissues from within their hosts, it is reasonable to suggest that internal parasitization would also influence host food consumption and metabolism. We report on the effects of parasitism by Cotesia flavipes on the food consumption and utilization of its host, Diatraea saccharalis. Cotesia flavipes reduces the host food consumption, but parasitized larvae considered a unit with their parasitoid's attained the same final weight as the nonparasitized larvae. Nutritional indices, midgut activities of carbohydrases, and trypsin of parasitized and nonparasitized D. saccharalis were assessed. Parasitized larvae had reduced relative food consumption, metabolic and growth rates, coupled with higher efficiency for conversion of the digested, but not ingested, food into body mass. Parasitism also affected food flux through the gut and protein contents in the midgut of parasitized larvae. The activity of -amylase and trehalase in parasitized host was enhanced in the first day after parasitism relative to control larvae. Saccharase activity remained unchanged during larval development. Trypsin activity was reduced from the fifth to ninth day after parasitism. We argue on the mechanisms involved in host food processing after parasitism.
Keywords: digestive enzymes; host regulation; parasitoid